Efek Imunostimulan Ekstrak Etanol Daun Seledri terhadap Mencit Putih Jantan - Erjon Nazir (Jurnal Penelitian Farmasi Indonesia, 2020)
The main active compound of celery is apigenin which is thought to have an immunostimulatory effect. This research aimed to evaluate the immunostimulatory effects of the ethanol extract of the celery leaf (Apium graveolens L.) using carbon clearance methods. The animal models used were albino mice male which were divided into 5 groups. Group I as negative control (tween 80%), group II, III, IV were given ethanol extract of celery leaves at a dose of 125 mg kgbw, 250 mg/kgbw, 500 mg/kgbw, and group V as the positive control (Stimuno Forte®). The dosage is given orally in a single dose for 6 days. The results showed the administration of test preparations with a dose of 125 mg/kgbw, 250 mg/kgbw, 500 mg/kgbw showed the phagocytosis constant value, half-life and leukocyte values ​​were significantly different from negative control (p <0.01). Phagocytosis indices from test preparations with a dose of 125 mg kgbw, 250 mg/kgbw, 500 mg/kgbw also show values ​​greater than 1. It was concluded that the ethanol extract of celery leaves at a dose of 125 mg kgbw, 250 mg/kgbw, 500 mg/kgbw is as immunostimulants.